UNIVERSITY NOTES. (The Accounting Review, 1928)
The article presents information about various activities taking place in several universities in the U.S. Scholar James P. Adams, chairman of the department of economics, Brown University was appointed in April, 1925, sole arbitrator in a dispute between Electric Railways Co. and the Providence division of the Amalgamated Association of Street and Electric Railway Employees. A.H. Ribbink, adjuct educator of accounting, University of Texas, has been granted a one year leave of absence to work with the Rand Kardex company. H.J. Fehn, associate educator of accounting leaves that position to assume duties as research specialist with the bureau of business research. Scholar Herschel Walling, has been appointed instructor in accounting. The thirteenth annual meeting of the American Association of University Instructors in Accounting will be held at the Hotel Stevens, Chicago, on December 27 to 28, 1928. Educator H.T. Scovil, University of Illinois, has been named a member of the Committee on the Natural Business Year of the American Institute of Accountants. Assistant educator H.H. Baily has returned from a year's leave of absence spent in travel and study in Europe.